Gender violence as genocide: the Rosa Lee Ingram case and We Charge Genocide petition. (24th February 2022) - Lynn, Denise
Abstract : In 1951, the Civil Rights Congress (CRC), under the leadership of William Patterson, submitted a 200+-page petition to the United Nations charging the United States with genocide against Black Americans. The meticulously researched petition documented hundreds of cases of assault, legal lynching (the use of the legal system to deny Black Americans justice) and death that all amounted to a system in which the federal government failed to protect Black Americans against injustice. Sexual assault figured prominently in the petition. This article looks specifically at the case of Rosa Lee Ingram as exemplary of both legal lynching and gender violence that were essential to the argument that the United States was guilty of genocide. For Patterson and the CRC, sexual violence and the threat of sexual assault, as in the Ingram case, was symptomatic of a larger terror campaign that focused on Black Americans, circumscribing their rights, their lives and safety, and confirming a white supremacist system that punished Black male sexuality and claimed Black women's sexuality for its own.